Implementation of Online Single Submission Policy at One-Stop Investment and Integrated Services in East Java - Sayogi, Sintania; Suhardono, Edi (Universitas Teuku Umar, 2023)
This study aims to analyze innovation governance in the Surabaya Teacher Application Information System (SIAGUS). Surabaya Teacher Application Information System (SIAGUS) is a web-based application designed for teachers and education personnel. This research uses Innovative Governance theory according to the United Nations (2015) which consists of several indicators, namely: Institutions, Policy Actors and Society. This research uses Innovative Governance theory according to the United Nations (2015) which consists of several indicators, namely: Institutions, Policy Actors and Society The method used in this study is descriptive qualitative with a case study approach. The informant determination technique is purposive sampling and choosing the informant key. Data collection techniques are observation, interview and documentation. The results showed that managing innovation is supported by various aspects such as institutional analysis, employee discipline, attitudes to serve the community, culture, and community participation. There are also those that have not been supported, such as regulations governing overall innovation, teacher knowledge and the process of utilizing technology. So that regulations are needed that regulate the Surabaya Teacher Application Information System (SIAGUS) and assistance to teachers.